Comprehensive comparison of cloud-based NGS data analysis and alignment tools. (2020) - Bani Baker, Qanita; Hammad, Mahmoud; Al-Rashdan, Wesam; Jararweh, Yaser; AL-Smadi, Mohammad; Al-Zinati, Mohammad
Abstract: Next-Generation Sequencing (NGS) is very helpful for conducting DeoxyriboNucleic Acid (DNA) Sequencing. DNA sequencing is the process for determining the order (sequence) of the main chemical bases in the DNA. Analyzing human DNA sequencing is important for determining the possibility that a person will develop certain diseases, and/or the ability to respond to medication. However, the NGS process is a complicated and resource-hungry technical process. To solve this dilemma, the majority of NGS software systems are deployed as cloud-based services distributed over cloud-based platforms. Cloud-based platforms provide promising solutions for the computationally intensive tasks required by the NGS data analysis. This work provides a comprehensive investigation of cloud-based NGS data analysis and alignment tools, both the commercial and the open-source tools. We also discuss in detail the main features and setup requirements for each tool, and then compare and contrast between them. Moreover, we extensively analyze and classify the studied NGS data analysis and alignment tools to help NGS biomedical researchers and clinicians in finding appropriate tools for their work, while understanding the similarities and the differences between them.